The Role of Lexical Units in Teaching A Foreign Language in The Field of Transport (International Journal of Scientific Trends, 2024)
The article examines the advancements in teaching a foreign language with a professional focus, focusing on socioeconomic factors and the shift from competency-based to cognitive models. The Department of Foreign Languages at Transport has contributed to this development through the creation of the "English in the field of Railway Transport" electronic educational complex. The article also introduces a multilingual learning environment based on Onto.plus ontologies, developed by the Educational and Methodological Center for Education in Railway Transport. The article emphasises the importance of developing methodologies to enhance students' cognitive abilities in learning a professionally oriented foreign language. This article is relevant to educators and students in transportation studies.